(untitled) (Journal of Agriculture & Rural Development, 2010)
The study was conducted at three villages under Birganj upazilla of Dinajpur district to select suitable mungbean genotype to fit in the rice-wheat-fallow cropping system. Nine advanced mungbean genotypes and a check variety were tested in the farmers’ fields through mother and baby trials managed by the farmers themselves. The mother trials were laid down in a radomized completely block design with three replications. Based on farmers’ judgment regarding field performances and post-harvest evaluation on growth, field duration, seed yield, taste, cooking and milling quality, VC3960-88 appeared as the most preferred genotype. Farmers also preferred VC6153B-20P next to the above genotype. The baby trials conducted in thirty farmers’ field reaffirmed that VC3960-88 was also the most preferred genotype. The performance of genotypes in baby trials and subsequent preference of the farmers signified the role of mother-baby trial approach towards selecting mungbean genotype by themselves. Key words: Variety, mungbean, selection, cropping system, PR & D approach. DOI: 10.3329/jard.v7i1.4419 J Agric Rural Dev 7(1&2), 33-40, June 2009